2021
DOI: 10.56126/72.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study to assess neutrophil and endothelial response to knee arthroplasty with the use of a tourniquet : effects of spinal or sevoflurane anesthesia

Abstract: Background : During orthopedic surgery, the use of a pneumatic tourniquet results in side effects secondary to ischemia-reperfusion phenomena. We tested the hypothesis that total knee arthroplasty with a tourniquet is associated with increase in plasma concentrations of biomarkers of neutrophil activation and endothelial injury. The second aim was to compare these changes during spinal or general inhalational anesthesia. Methods : 40 adult ASA I-II patients scheduled for total knee arthroplasty with a tourniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Animal and human studies have shown that opioid-mediated myocardial protection may be associated with improving ischemia-reperfusion injury. [15][16][17] The 3 different opioid receptor subtypes, κ, μ, and δ, appear to play different roles in producing these effects. [18] The combination of butorphanol and sufentanil may make the protective effect on the myocardium more significant.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies have shown that opioid-mediated myocardial protection may be associated with improving ischemia-reperfusion injury. [15][16][17] The 3 different opioid receptor subtypes, κ, μ, and δ, appear to play different roles in producing these effects. [18] The combination of butorphanol and sufentanil may make the protective effect on the myocardium more significant.…”
Section: Discussionmentioning
confidence: 99%